Positioning accuracy analysis of the parallel mechanism near singular positions - Bałchanowski, Jacek (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a method of numerical modelling of parallel mechanisms with clearances in their kinematic pairs taken into account. The pairs with clearances are modelled as shape connections based on constraints in the form of contact interactions. Using the created models simulations were run to determine the positioning errors of the links in a parallel mechanism with three degrees of freedom (MR2120). In particular, the accuracy of positioning the links close to the mechanism singular configurations was studied.
Keywords: clearances in the joint; parallel mechanism; singular positions